Cardiomyopathy as indication for pediatric heart transplantation - Alireza Raissadati, MD/PHD; Drishti Tolani, MD; Elizabeth L. Profita, MD (JHLT Open)
Pediatric cardiomyopathy (CMP), with an incidence of approximately 1 in 100,000 children, remains a critical clinical challenge. Often progressive, these myocardial disorders frequently culminate in end-stage heart failure, establishing CMP as the primary indication for pediatric heart transplantation. Key considerations for transplantation include specific CMP etiologies and subtypes alongside established listing criteria and strategies to navigate waitlist complexities. The evolving role of mechanical circulatory support, especially ventricular assist devices (VADs), has transformed bridging strategies and significantly improved survival to transplant. Contemporary post-transplant outcomes demonstrate continued improvement, with advancements in survival rates and ongoing refinement of essential long-term management strategies. This review provides a comprehensive analysis of pediatric CMP as it progresses to end-stage heart failure requiring transplantation. It synthesizes current knowledge on etiologies, clinical presentations, transplant evaluation, the transformative impact of VADs, and contemporary post-transplant management, aiming to equip clinicians with an updated framework for complex decision-making and optimizing outcomes in this high-risk population.